Variable crop residue management - Myers, Brian (Kansas State University, 2015)
Production agriculture is constantly evolving to become more efficient and productive. Crop residue serves as a valuable source of nutrients for the soil, but it is increasingly abundant with today’s enhanced crop genetics. If new technology can effectively provide a way to micro-manage crop residue levels within a field, the benefits will go beyond soil health. Surplus crop residue can be collected for secondary income while leaving the optimum amounts in the field to maintain the environment and soil health as well as promote future crop growth. The main objective of this study is to create a budget model that will determine the economic impact of crop residue removal on a controlled basis. The goals are to determine crop residue removal practices that are sustainable for the long-term, while also enhancing soil quality and increasing grain yield in future years. A sub-objective is to build a business case for producers to invest in variable crop residue management. The hypothesis presented in this study is that the increased complexity and price of a variable rate system is offset by more supplemental profits, increased crop yields, and better management of soil health and nutrients. The negative perceptions of crop residue removal include the fear of soil erosion or loss of soil organic matter. By developing a budget model that is easy to use, takes advantage of existing field data for inputs, and allows producers the ability to look at their operations on a sub-field level, this study aims to provide the necessary motivation to invest in new technology that will increase their productivity. By entering their site-specific crop residue return rate data into a budget model, along with prices and costs related to combine and auxiliary equipment, corn and corn stover, transportation and logistics, and nutrient replacement, they will come up with a return per acre for both constant rate and variable rate collection. The budget model determines whether it is economically viable to harvest crop residue from a continuous corn rotation at a variable rate across a field, rather than at a constant rate, using a producer’s own specific field data. To validate the concept, data from a joint study between John Deere and Iowa State is entered into the model. Prescriptions for corn stover return rates are provided from the study for pre-defined grid areas. Prescriptions are derived from a combination of data including grain yield, soil loss due to wind and water erosion, climate, topography, and soil sample data at time of planting (Nelson, et al. 2004). The average corn stover removal percentage was less for variable rate collection than constant rate collection, 26.05% to 31.85%. However, the assumption that grain yield and corn stover yield are positively correlated did not prove to be true in this case study. The variable rate plots had a lower average grain yield of 158.84 bushel/acre, compared to 160.46 for the constant rate plots, but they had more total corn stover available and therefore a higher return rate of 3.70 tons/acre, compared to 3.05 for the constant rate plots. This case study illustrates that less corn stover can be returned to the field through constant or variable rate collection while sustaining higher grain yields than a conventional harvest that would return all of the corn stover to the field. This case study demonstrates that variable rate collection can be more expensive than constant rate, but not in every situation. Every unique field site will require a specific crop residue management recommendation that is determined by both economic and environmental factors.
Keywords: Crop residue